Programming reactive extensions and LINQ - Liberty, Jesse (Apress, 2011)
Pro Reactive Extensions and LINQ is a deep dive into the next important technology for .NET developers: Reactive Extensions. This in-depth tutorial goes beyond what is available anywhere else to teach how to write WPF, Silverlight, and Windows Phone applications using the Reactive Extensions (Rx) to handle events and asynchronous method calls. Reactive programming allows you to turn those aspects of your code that are currently imperative into something much more event-driven and flexible. For this reason, it's sometimes referred to as LINQ for Events. Reactive programming hinges on the concept of the observable collection, as opposed to the simple enumerable collection with which we?re all familiar. For example, to extract data from a collection and add it to a list box, you would traditionally iterate through the list box, extracting each object in turn. This approach works fine, but it requires significant knowledge about the data you're working with, which can be limiting. In Rx programming, you're instead informed about each object in turn and then free to react to each notification however you like, which affords much greater flexibility. This book shows you how reactive programming can be applied to a range of situations from WPF applications to Windows Phone apps to improve coding efficiency and boost performance.